Combined transcriptome and proteome analysis of Bcfrp1 involved in regulating the biosynthesis of abscisic acid and growth in Botrytis cinerea TB-31 - Chen, Dongbo; Shu, Dan; Wei, Zhao; Luo, Di; Yang, Jie; Li, Zhemin; Tan, Hong (Frontiers in Microbiology, 2023)
Abscisic acid (ABA) is an important sesquiterpene compound that regulates the stress resistance of plants. Botrytis cinerea can synthesize ABA via the mevalonic acid pathway. To identify the functional genes that are involved in the biosynthesis of ABA, we performed insertion mutagenesis and obtained the mutant E154 that produces less ABA compared with the parental strain B. cinerea TB-31. Thermal asymmetric interlaced PCR identified the insertion site, which was located upstream of the gene bcfrp1. This gene encodes an F-box protein. We performed a detailed phenotypic characterization of the bcfrp1 knockout and complementation mutants in TB-31. The phenotypic results confirmed the positive contribution of bcfrp1 to the biosynthesis of ABA and growth. Furthermore, transcriptome and proteome analyses were conducted to explore how bcfrp1 affects the level of the ABA biosynthesis. Between TB-31 and ΔBcfrp1, we obtained 4,128 and 1,073 differentially expressed genes and proteins, respectively. The impaired ABA biosynthesis in the ΔBcfrp1 mutants was primarily affected by the different levels of expression of the ABA biosynthetic gene cluster and the genes involved in the mevalonic acid pathway. In addition, we further characterized the differentially expressed genes and proteins that participated in the growth, secondary metabolism, and signal transduction in B. cinerea based on the transcriptome and proteome data. This research based on the transcriptome and proteome analyses to display the changes after the deletion of bcfrp1 in B. cinerea TB-31, will help us to explore the molecular mechanism of ABA biosynthesis in B. cinerea.